Pengaruh Pemberian Pupuk N dan Campuran Kompos Tandan Kosong Kelapa Sawit Dengan Abu Boiler Terhadap Pertumbuhan dan Produksi Tanaman Padi - Neni Natasia; Nelvia '; Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aim of riset of Nitrogen fertilizer and Palm Oil Empty Bunches (POEB) compost mixture with boiler ash to increase growth and rice yield. Research was conducted at Pulau Rambai village, Kampar, from December 2012 to March 2013. The method used Randomized Complete Block Design (RCBD) factorial consisting of 2 factors. The first factor is the provision of 5 tons of compost and boiler ash which consists of 4 levels that are0, 500, 750, and 1000 kg/ha. The second factor of nitrogen fertilizer with 2 level,(100 kg N/ha and 200 kg N/ha ). On this research obtained 8 treatment combination with 3 replications. Research result indicate that the provision of 5 tons of compost and 1000 kg/ha boiler ash ash followed by N fertilizer significantly different on  plant height, maximum number oftillers, number of productive tillers, grain weight. Keyword :Compost, boiler ash, nitrogen, rice